Single Series and Double Shunt SPDT Switch with Defected Ground Structure for Wireless Data Communication at 2.4 GHz Band - Shairi, Noor Azwan; Ahmad, Badrul Hisham; Anuar Faidz, Osman (2010)
A design of single series and double shunt of single pole double throw (SPDT) switch with defected ground structure (DGS) is presented in this paper. SPDT switch is commonly used in a RF transceiver system in modern wireless data communication system to perform time division duplex (TDD) switching for transmit and receive operation. The implementation of DGS in this switch has reduced 35% of the transmission line length and thus, reducing the circuit board size. The performances of SPDT switch with DGS such as insertion loss and isolation are comparable with the normal SPDT switch.